An Exploration of Students' Perspectives on the Use of Digital Media in English Language Learning at SMAN 10 Surabaya - Umar, Aisya Fadila Firdaus; Rakhmawati, Rakhmawati; Kurniawati, Bachrijah (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to explore the perspectives of eleventh-grade students at SMAN 10 Surabaya on the use of digital media in English language learning. The study focuses on their classroom experiences during a teaching practice where various digital tools were integrated into lessons. Using a descriptive quantitative design with qualitative interpretation, data were collected through questionnaires distributed via Google Forms. The data were analyzed using descriptive quantitative analysis, involving percentage summaries and qualitative interpretation to describe students’ overall perceptions. The study evaluated students’ satisfaction, perceived benefits, motivation, and their understanding of grammar through digital media. The results revealed that students generally had positive perceptions of digital media, reporting increased motivation, engagement, and improved comprehension. However, a few students encountered difficulties related to digital literacy and performance pressure during gamified learning. These findings imply that teachers should integrate digital media tools strategically to create engaging, student-centered learning environments. Teachers are encouraged to balance interactive and competitive elements with supportive feedback to ensure that all students feel comfortable and confident during digital activities. Future research could combine quantitative data with in-depth interviews to gain a more comprehensive understanding of students’ experiences and challenges in using digital media.